DARE Newsletter, Vol. 11, No. 1, Winter 2008 - DARE; Hall, Joan Houston; Henderson, Michael M.T. (Dictionary of American Regional English, 2008)
Contents: "How Much of a Good Thing Is Too Much?" by Joan Houston Hall; "DARE in the Early Seventies" by Michael M.T. Henderson; "DARE Editor Steps Down as Dictionary Society Exec"; "Contributors to DARE in 2007"; "Students Search the Internet for DARE"; "DARE's Loss Is Lansing's Gain"; "DARE Editors Attend Conference"; "Word Mavens Fete DARE"; "Pictures from the New York Times Event"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: English Language--Dialects--United States; Americanisms; Dictionaries; Lexicography; Regional English; Fieldwork